Mechanistic insights into the Orai channel by molecular dynamics simulations. (October 2019) - Bonhenry, Daniel; Schober, Romana; Schmidt, Tony; Waldherr, Linda; Ettrich, Rüdiger H.; Schindl, Rainer
Abstract: Highly Ca 2+ selective channels trigger a large variety of cellular signaling processes in both excitable and non-excitable cells. Among these channels, the Orai channel is unique in its activation mechanism and its structure. It mediates Ca 2+ influx into the cytosol with an extremely small unitary conductance over longer time-scales, ranging from minutes up to several hours. Its activation is regulated by the Ca 2+ content of the endoplasmic reticulum (ER). Depletion of luminal [Ca 2+ ]ER is sensed by the STIM1 single transmembrane protein that directly binds and gates the Orai1 channel. Orai mediated Ca 2+ influx increases cytosolic Ca 2+ from 100 nM up to low micromolar range close to the pore and thereby forms Ca 2+ microdomains. Hence, these features of the Orai channel can trigger long-term signaling processes without affecting the overall Ca 2+ content of a single living cell. Here we focus on the architecture and dynamic conformational changes within the Orai channel. This review summarizes current achievements of molecular dynamics simulations in combination with live cell recordings to address gating and permeation of the Orai channel with molecular precision.